Remoção de compostos ácidos do petróleo em diferentes tipos de carvão ativado - Araújo, Anderson Barros Caixeta (2016)
The naphthenic acids comprise a complex mixture of carboxylic acids that are present in petroleum. They are directly responsible for the oil acidity and its corrosiveness in liquid phase during the refining process. Such compounds are also presents in the derivatives, causing several problems to product quality. A possible way of removing these acids from those oil fractions is using the adsorption process in porous solids, as activated carbons. There are few studies about the removal of naphthenic acids on coals. For this reason, we chose four types of activated carbons for adsorption tests, and they coal babassu, palm kernel, coconut and of Bahia ox bone. In order to assess the possibility of further removing acidic compounds, the four carbons were subjected to a chemical treatment with concentrated sodium hydroxide. Physical and chemical analyzes were performed in order to promote the characterization of all adsorbents, showing that the treatment previously mentioned was leading to an increase in the adsorption capacity of the coals. The adsorption experiments with commercial batch naphthenic acid solution showed that the treated ox bone char had the highest retention efficiency, which is the adsorbent used to construct the adsorption isotherms. The isotherms were better adjusted by Langmuir model, revealing the chemisorption of character adsorptive process. The thermodynamic data showed that the process is spontaneous and endothermic, is favored by increasing the temperature. Regarding the crude oil sample, batch adsorption experiments were conducted in such a way as to determine the removal efficiency of class O2 and reducing the Total Acid Number (IAT). The results spectrometry FTICR ix MS Pasta, they showed that all coals chemically treated were able to remove more acidic compounds in relation to their untreated related. The raw coals babassu oil, palm oil and coconut Bahia showed a potential for adsorption of nitrogen compounds from oil, given that there was a decrease in its class in the class chart. As a final analysis, all the coals were evaluated for their ability to lower oil IAT, it was found that the ox bone char treated again achieved the best result, reducing by 70% the value of the IAT.